The Orphan Response Regulator Rv3143 Modulates the Activity of the NADH Dehydrogenase Complex (Nuo) in Mycobacterium tuberculosis via Protein–Protein Interactions - Płocińska, Renata; Wasik, Karolina; Płociński, Przemysław; Lechowicz, Ewelina; Antczak, Magdalena; Błaszczyk, Ewelina; Dziadek, Bożena; Słomka, Marcin; Rumijowska-Galewicz, Anna; Dziadek, Jarosław (Frontiers in Cellular and Infection Microbiology, 2022)
Two-component signal transduction systems enable mycobacterial cells to quickly adapt and adequately respond to adverse environmental conditions encountered at various stages of host infection. We attempted to determine the role of the Rv3143 “orphan” response regulator in the physiology of Mycobacterium tuberculosis and its orthologue Msmeg_2064 in Mycobacterium smegmatis. We identified the Rv3143 protein as an interaction partner for NuoD, a member of the type I NADH dehydrogenase complex involved in oxidative phosphorylation. The mutants Δrv3143 and Δmsmeg_2064 were engineered in M. tuberculosis and M. smegmatis cells, respectively. The Δmsmeg_2064 strain exhibited a significant reduction in growth and viability in the presence of reactive nitrogen species. The Rv3143-deficient strain was sensitive to valinomycin, which is known to reduce the electrochemical potential of the cell and overexpressed genes required for nitrate respiration. An increased level of reduction of the 2,3,5-triphenyltetrazolium chloride (TTC) electron acceptor in Δrv3143 and Δmsmeg_2064 cells was also evident. The silencing of ndh expression using CRISPRi/dCas9 affected cell survival under limited oxygen conditions. Oxygen consumption during entry to hypoxia was most severely affected in the double-mutant Δmsmeg_2064 ndhCRISPRi/dCas9. We propose that the regulatory protein Rv3143 is a component of the Nuo complex and modulates its activity.